2006
DOI: 10.1080/00016480500452509
|View full text |Cite
|
Sign up to set email alerts
|

Hyalinizing clear cell carcinoma arising from the base of the tongue

Abstract: Hyalinizing clear cell carcinoma is a low-grade indolent and rare salivary gland tumor originally described by Milchgrub et al. in 1994. We herein report a case of this tumor of the base of the tongue. A 66-year-old Japanese woman presented with a large painless mass in the throat. Computed tomography and magnetic resonance imaging revealed a 40x30-mm well-defined ovoid tumor arising from the base of the tongue. She underwent tracheostomy followed by a resection of the tumor via the transmandibular approach co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 4 publications
(7 reference statements)
0
21
0
Order By: Relevance
“…Our review of the literature revealed 130 cases of HCCC among 48 articles . We did exclude a number of articles that have been reported by others to represent HCCC but, in our view, did not provide sufficient histologic description to confirm the diagnosis .…”
Section: Resultsmentioning
confidence: 98%
“…Our review of the literature revealed 130 cases of HCCC among 48 articles . We did exclude a number of articles that have been reported by others to represent HCCC but, in our view, did not provide sufficient histologic description to confirm the diagnosis .…”
Section: Resultsmentioning
confidence: 98%
“…Of 153 patients with some form of clinical data reported or available, 144 underwent primary surgical resection. Lymph node dissection was reported in 26 cases, with positive nodes in 13 . Neck dissection, where specified, was usually unilateral, and limited to supraomohyoid levels I to III.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical and pathologic features of the 44 published patients with HCCC who we identified in our review of the literature are summarized in Table 3 1, 3–26. Thirty‐one tumors (72%) occurred in women, 12 tumors (28%) occurred in men, and, in 1 tumor, the sex of the patient was not stated.…”
Section: Resultsmentioning
confidence: 99%